Improving IT Team Motivation in Using IT Helpdesk - Cynthia Dewi Tanuraharja; Gunawan Wang (Universitas Bina Darma, 2022)
Information Technology and Information Systems are important in supporting operations in a company. The organization's ability to manage IT affects the quality of its information technology services, especially in the use of the IT Helpdesk. The IT Helpdesk acts as a good service provider for request fulfillment and problem management in the company and aims for the IT support team to monitor the status of work on problems faced by users and can analyze lead times from the emergence of these problems to their completion. The IT Helpdesk in a company engaged in the garment and textile industry has not been used optimally, for example, e-ticketing has not reached the target time specified in the Standard Operating Procedures (SOP) at the company due to a lack of enthusiasm and lack of motivation by the IT team towards the use of IT Helpdesk. Therefore, the researchers designed a prototype of the application of gamification with the Mechanics-Dynamics-Aesthetics (MDA) framework at the IT Helpdesk as a strategy used to increase the motivation and enthusiasm of the IT team that is useful for improving the performance of each IT team.